PENGARUH IKLAN DAN CITRA MEREK TERHADAP KEPUTUSAN KONSUMEN DALAM MENGGUNAKAN SEPEDA MOTOR HONDA JENIS SCOOPY - Juniarti, Shavnidar; Hendra, Hendra (I-Con Media, 2022)
The purpose of this study was to determine the effect of advertising and brand image simultaneously and partially on consumer decision in purchasing Honda Scoopy Motorbikes.Â The sample in this study was 87 students of SMA Negeri 1 Muara Badak who own Honda Scoopy motorbikes. The analysis tool used is multiple regression. Â The result of this study revealed that simultaneously advertising and brand image positively and significantly affect purchase decision.. Besides, partially, this study found that partially both brand image and advertising affect positively and significantly towards purchase decision respectively.